Motive, means, and opportunity - Bossley, L (Oxford Institute for Energy Studies, 2013)
When the European Commission (EC) swooped, like the SAS, into the offices of Shell, BP, Statoil, and Platts (the price reporting agency), on 14 May this year looking for evidence of manipulation of Platts prices, it seemed as if a major overhaul of the oil market, not just of oil price reporting, might be in the offing.